Nursing students' experience in a health education group: a dialogic approach - Kelly Cristina Lopes da Silva; Valéria Guimarães Bernardo; Nello Pereira da Silva; Danilo Cabral Ramos; Bruno Gomes Canha; Lucas Pereira de Melo; Luciana Cristina dos Santos Ribeiro (Universidade de Fortaleza, 2011)
Objective: To conduct a theoretical reflection on the experience of nursing students in a group of health education, in Campinas-SP, having as theoretical and methodological referential the Dialogical Model. Data Synthesis: This was an experience report, conductedin a Health Center of Southwest Health District, located in Campinas-SP, in the period from August to December 2009. This group was divided into 04 subgroups of on average 60 users each, being held diagnostic evaluation, identification of issues to be worked with users and planning and execution of group dynamics. The methodology developed in the educational activities was based on the theoretical Dialogical Model of Health Education. By means of group dynamics three changes were promoted in the way in which health education isthought and conducted: i) from a biologicist focus to the multidimensional apprehension of the individual; ii) through sharing, we learn: the principle of bidirectionality; iii) to know, not to know or do we know? The principle of symmetry. Conclusions: The viability and operability of the Dialogic Model for health education interventions is demonstrated.